The more the terrier ebook - Rosenfelt, David (Andy Carpenter, 2024)
The next installment in David Rosenfelt's bestselling Andy Carpenter series brings a lone pup to his doorstep, but when it comes to dogs, The More the Terrier . Reluctant lawyer Andy Carpenter is relieved to be headed back to Paterson, New Jersey, after a week-long family vacation in the Adirondacks. He's ready to put the holly jolly season way behind him and settle in at home with his three dogs. But when they finally arrive, there is an extra dog eagerly awaiting them, as well as one anxious dog sitter. When the dog showed up on the doorstep a few days ago, the sitter knew Andy would know what to do. Indeed, Andy recognizes Murphy, who the Carpenters fostered before the dog went home with BJ Bremer and his mother. BJ wanted to learn all he could about caring for Murphy, which made Andy like him immediately. When Andy goes to take Murphy back to the Bremers, though, instead of the happy reunion he expects, he finds BJ's mother in tears. It turns out Murphy ran off...after BJ was arrested for murder. Andy had hoped for a quiet Christmas vacation, but he likes Murphy's family and his golden retriever, Tara, likes Murphy, so he can't resist getting involved. The case isn't as simple as Andy thought it would be, though, with BJ suspected of murdering one of his professors. With nothing to go on but Andy's own conviction in BJ's dog-loving character, proving his innocence would be a Christmas miracle. With equal doses of doggy humor and courtroom drama, as well as Andy Carpenter's traditional humbug Christmas spirit, David Rosenfelt delivers another winner.